Can the Straw Remaining on the Ground Reduce the Wheelsets Impact on Sugarcane Crop? - Marques Filho, Aldir Carpes [UNESP]; de Medeiros, Simone Daniela Sartório; Martins, Murilo Battistuzzi; dos Santos Moura, Michel [UNESP]; Lanças, Kléber Pereira [UNESP] (Springer Nature, 2022)
Sugarcane is one of the most important agricultural crops in the Brazilian trade economics, however, this crop presents challenges in maintaining the physical structure of the soil throughout the production cycle. The ground cover has a direct interference in the compaction processes. However, the amount to be kept in the field remains a difficult to discover unknown. The aim of this study was to evaluate the tread–soil interaction and penetration resistance provided by 600/50–22.5 bias-ply agricultural tire, under three different amounts of straw on the surface: 0, 15 and 30 Mg ha−1. The tests were carried out at the Nempa Center Testing of Agroforestry Machines and Tires, UNESP/Botucatu–SP. The Fixed Tire Testing Unit was used, applying a constant and controlled load to the tire on standardized soil with different amounts of straw on the surface. The response to variables analyzed was the settlement contact area and the resistance soil penetration (RSP). The findings of the study showed that amount of straw on the ground attenuates the impact of wheelset on the soil and linearly increases the area of wheelhouse–soil interaction (r2 = 0.98), contact width (r2 = 0.97), contact length (r2 = 0.86) and depth (r2 = 0.99). The RSP is linearly inverse (r2 = 0.97) to the amount of straw in the covering, where 15 Mg ha−1 was found adequate to maintain soil quality due to machine traffic under the conditions analyzed.
Keywords: Biomass; Compaction; Cone index